Factors that drive green building implementation and the cost impact of green building implementation - Muhamad Fadhil, Abdul Halim (2015)
This research is discuss about the factors that drive the green building implementation and the cost impact of green building implementation. The first objective of this research are to identify the factors that drive the contractors to implement green building practices in their project at the same time to analysed the cost impact when implementing green building practice in their project. Two type of data collecting technique are used in order to collect the data on the topic. The primary data are obtained through the survey of questionnaires that have been send to the total of 112 G7 contractors registered under CIDB located in Lembah Klang. Secondary data are collected through the website, reading the journal, articles and books in library. Based on the data analysis in chapter 4, in can be conclude that most of the respondent are agree that the issues of environmental problem including air pollution, global warming and carbon dioxide emission is the main factor that drive the contractors to implement green building practice. Meanwhile, the finding also shows that the green building practice will hugely give an impact on the lifecycle cost of the building such as reduce operation cost and utility cost. As the conclusion, in order to reduce the impact of built environment on people and environment, green building concept is the most applicable approaches.